Matrix Metalloproteinase (MMP) 9 Transcription in Mouse Brain Induced by Fear Learning - Ganguly, Krishnendu (American Society for Biochemistry and Molecular Biology, 2013)
Memory formation requires learning-based molecular and structural changes in neurons, whereas matrix metalloproteinase (MMP) 9 is involved in the synaptic plasticity by cleaving extracellular matrix proteins and, thus, is associated with learning processes in the mammalian brain. Because the mechanisms of MMP-9 transcription in the brain are poorly understood, this study aimed to elucidate regulation of MMP-9 gene expression in the mouse brain after fear learning. We show here that contextual fear conditioning markedly increases MMP-9 transcription, followed by enhanced enzymatic levels in the three major brain structures implicated in fear learning, i.e. the amygdala, hippocampus, and prefrontal cortex. To reveal the role of AP-1 transcription factor in MMP-9 gene expression, we have used reporter gene constructs with specifically mutated AP-1 gene promoter sites. The constructs were introduced into the medial prefrontal cortex of neonatal mouse pups by electroporation, and the regulation of MMP-9 transcription was studied after contextual fear conditioning in the adult animals. Specifically, −42/-50- and −478/-486-bp AP-1 binding motifs of the mouse MMP-9 promoter sequence have been found to play a major role in MMP-9 gene activation. Furthermore, increases in MMP-9 gene promoter binding by the AP-1 transcription factor proteins c-Fos and c-Jun have been demonstrated in all three brain structures under investigation. Hence, our results suggest that AP-1 acts as a positive regulator of MMP-9 transcription in the brain following fear learning.